MAKROZOOBENTUS DALAM BUDIDAYA POLIKULTUR DESA SAWOHAN SIDOARJO - Agustini, Maria; Muhajir, Muhajir; Icak, Icak (JHP17 (Jurnal Hasil Penelitian), 2019)
The research was about "Macrozoobenthos Diversity in Polyculture in Sawohan Village, Sedati, Sidoarjo. " conducted in Sawohan Village, Sedati, Sidoarjo in December 2018 until May 2019. This research was using purpose of the study was to determine the macrozoobenthos community structure which includes water quality percentages which influenced the abundance of macrozoobenthos in the Polyculture Cultivation pond in Sawohan Village, Sedati, Sidoarjo. This research was using a descriptive method of abundance of macrozoobenthos in Sawohan, Sedati, Sidoarjo. Data is collected by making observations and recording systematically both directly and indirectly at the research site. This research consisted of five stations,the first located on the pond plot inlet, station 2 was in the corner of the pond that was parallel to the inlet, station 3 was in the middle of the pond plot, station 4 was in the pond plot outlet, station 5 was in the corner of the pond parallel to the outlet. The results of the study found 6 types of macrozoobenthos spread in 5 research stations, there are: 1. Tescopium telescopium, 2, Cerithidea cingulata, 3. Rhinoclavis aspera, 4. Cerithium kobelti, 5. Cerithium alveolum, 6. Corbula faba hinds. The highest abundance of macrozoobenthos was found at the station 4, while the lowest value was found at the station 2. The highest diversity index was found at the station 2 and the lowest was found at the station 3. The highest Dominance index value was found at the station 3 while the lowest value was found at the station 2. Water quality at 5 observation stations within normal limits, and there is a correlation between water quality and macrozoobenthos abundance which has a strong correlation.Keywords: Macrozoobenthos, polyculture cultivation, diversity